The barriers of Industrialisation Building Sytem (IBS) adoption in Malaysian construction industry / Nursuhanis Bahadun and Nurul Huda Muhamad - Bahadun, Nursuhanis; Muhamad, Nurul Huda (2023)
Industrialized Building Systems (IBS)refer to various pre-fabricated construction methods. IBS components are constructed separately beforehand, and they are assembled on-site afterwards. In Malaysia, IBS has improved building quality, productivity, occupational safety and health concerns, and reduced construction costs. However, the adoption of IBS in the construction sector remains low due to limited modernization of construction procedures and methods. To fully implement IBS, efforts must be made to change current construction methods and train employees with specialization skills, such as coordination and installation. Thus, the aim of this research is to study the barrier of IBS adoption in Malaysian construction industry. The research objective for this study is to determine the main barriers of IBS adoption in Malaysian construction industry. The approach used for data collection for this study is quantitative method. The questionnaire were distributed to the IBS practitioners. The findings from this research revealed that the barriers of IBS adoption in Malaysian construction industry are lack of skill labour, high labour cost and high capital cost. This study will be beneficial to improve the level of IBS implementation in Malaysia.